Numerical investigation of mechanical behavior of human femoral diaphysis in normal and defective geometry: experimental evaluation. Issue 6 (26th April 2021) - Mahmoudi, Moeinoddin; Mahbadi, Hossein
Abstract: Failure and major reoperation after internal fixation (IF) in mature femoral bones are common and proper selection of fixation method may reduce the rate of reoperations. Investigating the mechanical behavior of the human femoral diaphysis, this article studies effect of mechanical properties and geometry of the bone on selection of IF method. To this aim, we calculated the bone mineral density in human femurs, and then, using computed tomography scan, we obtained geometry and nonhomogeneous properties of the bone. Finite element (FE) models of osteotomised femurs were reinforced using four types of screws with a locking compression plate (LCP). We performed buckling and 4-point bending simulations, and results of these simulations represent critical buckling loads, maximum von Mises stresses, and strains around the screws and the central defect. To evaluate FE analysis, we employed the compressive experiments and compared load vs. displacement curves with FE results. Results corresponding to intact, osteotomised, and reinforced states are compared together, and the effect of cortical and unicortical screws in LCPs is studied. The FE results showed that application of identical prophylactic IF for two persons with identical injuries in the same conditions bring quite inverse results. As a consequence, evaluation of osteoporosis, elastic modulus, and morphometric data are required before fixation and screw selection. Besides, for short diaphysis, unicortical screws have maximum strengthening factor in bending. While for long samples, these types of screws can be the worst option, application of cortical screws results to maximum strength in comparison with other types.